Entropy generation analysis of (CH2OH)2 containing CNTs nanofluid flow under effect of MHD and thermal radiation. (September 2019) - Hosseinzadeh, Kh.; Asadi, A.; Mogharrebi, A.R.; Khalesi, Javad; Mousavisani, Seyedmohammad; Ganji, D.D.
Abstract: Entropy generation of nanofluids between two stretching rotating discs under the effect of magnetohydrodynamic (MHD) and thermal radiation is examined in this work. In this paper, Ethylene glycol (CH2oH)2 is used as based fluid and Carbon nanotubes (CNTs), which include both single-walled carbon nanotube (SWCNT) and multiwall cabin nanotube (MWCNT), are used as nanoparticles. The nonlinear governing equations are solved using the Runge-Kutta method and the effects of the radiation parameter, magnetic field, porosity, suction/injection and Brinkman number on skin friction coefficient and Nusselt number are investigated. Additionally, the effects of these parameters on total entropy generation and the Bejan number are explored. The results are compared to two different nanoparticles and the results showed that the total entropy generation rises with increasing the thermal radiation and volume fraction of nanoparticles.